2022
DOI: 10.3390/ijms23031278
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Systemic Dexamethasone Regulates the Mineralocorticoid/Glucocorticoid Pathways Balance in Rat Ocular Tissues

Abstract: Central serous chorioretinopathy (CSCR) is a retinal disease affecting the retinal pigment epithelium (RPE) and the choroid. This is a recognized side-effect of glucocorticoids (GCs), administered through nasal, articular, oral and dermal routes. However, CSCR does not occur after intraocular GCs administration, suggesting that a hypothalamic-pituitary-adrenal axis (HPA) brake could play a role in the mechanistic link between CSCR and GS. The aim of this study was to explore this hypothesis. To induce HPA brak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…PLAUR is a crucial gene in chronic pruritus and functions through E1-PLAUR signaling [ 61 ]. Besides, one animal study showed that PLAUR played negative feedback regulation of glucocorticoid pathways in rats' ocular tissues [ 62 ]. Some scholars have found that PLAUR facilitated paclitaxel resistance and endometrial cancer cell invasiveness [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLAUR is a crucial gene in chronic pruritus and functions through E1-PLAUR signaling [ 61 ]. Besides, one animal study showed that PLAUR played negative feedback regulation of glucocorticoid pathways in rats' ocular tissues [ 62 ]. Some scholars have found that PLAUR facilitated paclitaxel resistance and endometrial cancer cell invasiveness [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We are interested in reading the in vitro study cited by Menean et al 1 concerning the implications of the differential expression of receptors for glucocorticoid hormones in rat ocular tissues in an experimental model of hypothalamic–pituitary–adrenocortical axis downregulation. 18 However, from the currently available literature, we do not believe it is possible to establish or even exclude a link between salivary α-AMY changes and glucocorticoid receptors (both mineralocorticoid and glucocorticoid receptor) in humans with acute/chronic CSC. 2 , 15 17 , 19 , 20 …”
mentioning
confidence: 84%
“…A curious phenomenon is the relative lack of CSCR development following intraocular corticosteroid injections. Zola et al hypothesized that the hypothalamic-pituitary-adrenal axis is inhibited by intraocular corticosteroids [45]. To test their hypothesis, rats were injected with intraocular dexamethasone daily for five days, and levels of corticosterone in ocular media were measured on day five.…”
Section: Mineralocorticoid Agonism and Central Serous Chorioretinopathymentioning
confidence: 99%